Fragile identities : towards a theology of interreligious hospitality - Moyaert, Marianne. (Currents of Encounter, 2011)
Interreligious dialogue is one of the major challenges confronting contemporary theology. In particular, the so-called "dialogical tension" between openness and identity has been a central issue: Can one maintain one's religious identity without closing oneself off from the other? In general, Christian reflection on interreligious dialogue begins with a theological reflection on religious plurality that assumes that one cannot engage seriously in interreligious dialogue without a sound theology of religions. In this book Marianne Moyaert critically assesses the various models for a Christian theology of religions (exclusivism, inclusivism, pluralism, particularism) by asking how these models relate to the dialogical tension between openness and identity. She argues that we need to overcome the classical theological approach of religious plurality and move in the direction of a theological hermeneutics of interreligious hospitality. To that end she turns to the French philosopher Paul Ricoeur, whose philosophical and hermeneutical insights can give a new turn to the discussion of the criteria, possibilities, and particularly the limits of interreligious dialogue.